An Analysis of Corporate Governance Disclosure Practices of BSE 200 Indian Companies - Kaur, Jagdeep (Indian Journal of Finance, 2025)
Purpose : The study examined the corporate governance (CG) disclosure practices of BSE 200 Indian companies and also focused on the extent of variation in the scoring of the companies during 2015 and 2023. Methodology : It examined the disclosure practices of 142 Indian firms listed on the BSE Sensex from the period of 2015 to 2023, based on secondary data. A â€œdichotomous methodâ€ was conducted to examine CG disclosure, and an index of CG was created. A total of 30 item parameters had been chosen from the CG section of the annual reports. Additionally, the paired sample t-test was employed to gauge the degree of score variability throughout the measurement period. Findings : The results showed that out of 142 BSE companies, Infosys Ltd. scored first, followed by ITC Limited and Mahindra and Mahindra Ltd., respectively, and it also revealed that there was significant variability in scores for the years 2015 and 2023. The results of the paired sample t-test indicated that the scores acquired in 2022â€“2023 were higher than the scores in 2014â€“2015. Practical Implications : These findings will help BSE regulators in formulating the disclosure practices requirement. The authors pointed out that corporate India has more motivation to follow CG reforms when there is an independent regulator in place with the authority to take action against offenders. Originality : It included the incorporation of a CG scorecard, a significant innovation presented in this paper.